Knowledge and perception of young students in Social Work about young people under guardianship - ESTRADA-MORENO, IRENE SOLEDAD; RUIZ-MOSQUERA, ANA CRISTINA; PALMA-GARCÍA, MARIA DE LAS OLAS (Acciones e Investigaciones Sociales, 2024)
There is currently an increase in the number of young people who find themselves in a situation of legal emancipation without social autonomy after leaving the child protection system at the age of majority. This group is socially disadvantaged and prone to social exclusion. Social work is key to intervene and change this reality, but more knowledge and training on this group is needed. The aim of this study is to identify the degree of knowledge and perception of students of the Degree in Social Work about the situation of young extuted. Material and methods: the present research is carried out from a descriptive and observational approach with the intention of approaching the knowledge of young ex-custodians from other young future professionals of their social intervention. A mixed methodology is used with surveys and a focus group with the participation of 250 students of the Degree in Social Work at the University of Malaga. Results: the perceived lack of knowledge that the young participants have of those who, at the same age, come from life experiences related to migration and lack of protection. It has been possible to identify training and guidance needs and strategies that can still be implemented within the framework of academic training. Discussion: the need to include and deepen the study and intervention of young people formerly under guardianship in order to improve their social inclusion and their relationship with other young university students has been identified.